Impact of Liquidity Management on Profitability of Joint Venture Banks in Nepal - Shrestha, Sanjay (Academic Voices: A Multidisciplinary Journal, 2020)
Liquidity management is one of the essential determinants of firms’ market value because it directly affects the profitability. This study investigates the impact of Liquidity management on profitability of joint venture commercial banks in Nepal. The objective of the study is to identify the relationship between the Liquidity management and profitability and its impact on profitability. The relation between the Liquidity management and profitability is examined using Descriptive statistic, Pearson correlation analyses and the effects on profitability is found out using the regression analyses by using a sample of 3 annual financial statements of joint venture commercial Banks in Nepal. The Liquidity management represents the variables of the Current Reserve Ratio (CRR), Credit Deposit Ratio (CDR), Capital Adequacy Ratio (CAR) and the profitability including return on equity (ROA)). The result revealed that the CDR is positively correlated with ROA while, CRR and CAR are inversely correlated with ROA. Thus, it could be concluded that CDR and CAR has significant impact on profitability and CRR has insignificant effect on Profitability of joint venture commercial banks in Nepal.